Analysis of Firm Value in Companies Listed in the LQ45 Index - Hariyono, Firmansyach Maulana; Nur, Dhani Ichsanuddin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the effect of profitability and liquidity on firm value with firm size as a moderating variable. The population of this research is 60 companies listed on the LQ45 index for the 2019-2022 period. The sample for this research was 27 companies that had been selected using a purposive sampling technique, then multiplied by 4 according to the research period so that there were 108 units of observation data. The analysis technique used in this research is Moderated Regression Analysis (MRA) using tools in the form of the SPSS application. Based on the results of data processing from this research, it can be concluded that profitability contributes to firm value. Liquidity also contributes to firm value. Meanwhile, firm size can moderate the influence of profitability and liquidity on firm value.